2019
DOI: 10.3847/1538-4357/ab48ff
|View full text |Cite
|
Sign up to set email alerts
|

An ALMA View of Molecular Filaments in the Large Magellanic Cloud. II. An Early Stage of High-mass Star Formation Embedded at Colliding Clouds in N159W-South

Abstract: We have conducted ALMA CO isotopes and 1.3 mm continuum observations toward filamentary molecular clouds of the N159W-South region in the Large Magellanic Cloud with an angular resolution of ∼0. ′′ 25 (∼0.07 pc). Although the previous lower resolution (∼1 ′′ ) ALMA observations revealed that there is a high-mass protostellar object at an intersection of two linear-shaped filaments in 13 CO with the length scale of ∼10 pc (Fukui et al. 2015), the spatially resolved observations, in particular, toward the highes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 78 publications
7
38
0
Order By: Relevance
“…In models v12GyTn and v12GyTy, most of the line-masses are sub-critical at t t fil (panels (e) and (g) in Figure 11), but they quickly evolve into supercritical ones by continuous accretion flows induced by the oblique shock in roughly 1 Myr (panels (f) and (h) in Figure 11). Recent observations suggest that high line-mass filaments greater than 100 M pc −1 are strong candidates for massive star progenitors (Fukui et al 2019;Shimajiri et al 2019;Tokuda et al 2019). We stress that such high line-mass filaments are naturally created in high shock velocity models in a short time.…”
Section: Filament Line Mass Functionmentioning
confidence: 72%
“…In models v12GyTn and v12GyTy, most of the line-masses are sub-critical at t t fil (panels (e) and (g) in Figure 11), but they quickly evolve into supercritical ones by continuous accretion flows induced by the oblique shock in roughly 1 Myr (panels (f) and (h) in Figure 11). Recent observations suggest that high line-mass filaments greater than 100 M pc −1 are strong candidates for massive star progenitors (Fukui et al 2019;Shimajiri et al 2019;Tokuda et al 2019). We stress that such high line-mass filaments are naturally created in high shock velocity models in a short time.…”
Section: Filament Line Mass Functionmentioning
confidence: 72%
“…Therefore, the surface brightness maps of CO lines can be a tool to understand the physical properties of star-forming clouds. The CO observations in the low-metallicity galaxies (such as LMC/SMC) are progressing (e.g., Fukui et al 2015;Muraoka et al 2017;Tokuda et al 2019). We plan to model the CO map to compare with the observations in a future study.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Myers 2009;Kirk et al 2013), to high-mass starforming regions (e.g. Peretto et al 2013;Schwörer et al 2019), and have even been observed in our closest neighbouring galaxy (Fukui et al 2019;Tokuda et al 2019). The formation mechanism of such hubs is not yet fully understood (see Myers 2009, for a description of possible mechanisms).…”
mentioning
confidence: 91%